"Auf dem richtigen Weg sein" - phraseodidaktische Ansätze im DaF-Unterricht - Valenčič Arh, Urška (Linguistica (Ljubljana), 2014)
Phraseological units are common linguistic elements, which have seen an upturn in phraseological research as well as in phraseodidactics of foreign language. Phraseology is used to expand the students' vocabulary and to enhance their communicative competence. Phraseodidactics deals with the treatment of phraseological vocabulary in language teaching practice and in course books. Its scope ranges from identifying phraseological units to developing students' phraseological competence in their mother tongue and/or foreign languages. The article deals with some aspects of the acquisition of phraseological competence in German as a foreign language. Special attention is given to the place phraseological units occupyin the coursebook and workbook for teaching German as a foreign language studio d - Die Mittelstufe B2. The focus is not only on the frequency of phraseological units, but on the didactic approach employed in dealing with such units as elements which should be systematically taken into consideration in teaching German as a foreign language. The article also discusses the importance of careful integration of phraseology into the Common European Framework of Reference for Languages as an important part of students' lexical competence at all levels from A1 to C2.
Keywords: allemand; frazem; frazeodidaktika; frazeologija; frazeološka enota; German; manuels de langue; nemščina; phraséodidactique; phraséologie; phraseology; tuji jeziki; učbeniki; unité phraséologique